On the Relationship between R&D and Productivity: a Treatment Effect Analysis - Giuseppe Medda; Claudio Piga; Donald Siegel (Fondazione Eni Enrico Mattei (FEEM), 2003)
This study uses firm level data from two detailed surveys of Italian manufacturing firms to study the relationship between R&D expenditures and productivity growth. The analysis considers the different contributions of various forms of R&D (product, process, internal, external in collaboration with universities, research centres and other firms) to Total Factor Productivity (TFP). Thus, this paper answers the call for more research on the links between a firm's external R&D and its productivity. In the cross-section econometric analysis, we estimate a Treatment Effects model based on the assumption that the decision to carry out R&D is endogenous. We found evidence supporting such a methodological approach. The main restlts reveal a positive and statistically significant relationship between the detailed measures of R&D and TFP. It is noteworthy that among external R&D investments, only expenditures for projects run in collaboration with other firms turn out to be highly significant, while cooperation in R&D with universities does not seem to lead to productivity enhancements. Because of the public good nature of research, firms may resort to do R&D within laboratories run by universities only when the outcome of the research does not have important strategic consequences.
Keywords: C21; C80; D24; O30; 330; Total factor productivity; selectivity; manufacturing; firm level; Forschung; Produktivität; Industrie; Italien